Investigation of curing period of cementitious adhesive and performance of rust prevention - Mimura, Yoichi; Vimonsatit, Vanissorn; Yoshitake, I. (The Geomate International Society, 2018)
A steel-concrete composite structure needs generally mechanical shear connectors such as headed studs to ensure efficient load resistances. As an alternative to shear studs, a type of cementitious adhesives has been developed to connect a steel-concrete composite structure. The unique feature of this adhesive is the improved bond performance with fresh concrete which depends on the curing age of the adhesive. This paper presents the outcome of fifteen flexural tests of elemental steel-concrete composite beams with various curing ages of the adhesive to investigate the appropriate curing period. Shot blasting steel plate and the un-shot blasting steel plate were prepared to examine the bond performance from the surface condition of the steel plate. The result of the flexural tests indicates that the bond performance between the steel plate and the concrete is optimum when the curing periods are 7 - 14 days. The tests with longer curing age produce similar bond performances with the tests at 7 days. Use of steel plate without shot blasting may be undesirable for the composite structure using the adhesive. In addition to the flexural tests, 8 deformed bars with and without adhesive coating were exposed to a field condition to investigate the rust preventive performance of the adhesive. The deformed bars without the adhesive had already corroded at 5 days after exposure. The observation showed the deformed bar with the adhesive was hardly deteriorated after 200 days.